The mediating role of PERMA in the relationship between social role engagement and drug use problems among veterans with mental illness - Campa, Rebecca; Solis, Guillermina R.; Koc, Muharrem; Granger, Teresa A.; Lee, Beatrice; Umucu, Emre (Frontiers in Psychiatry, 2025)
BackgroundSubstance use disorders (SUDs) are a critical issue among veterans, often co-occurring with mental illnesses and negatively impacting their well-being. This study explores the mediating role of well-being, as conceptualized by the PERMA model, in the relationship between ability to engage in social roles and activities and degree of problems related to drug abuse among veterans.MethodsData were collected from 156 veterans with self-reported mental health conditions. A parallel multiple mediation analysis using PROCESS macro assessed the role of PERMA components in mediating the relationship between ability to engage in social roles and activities and degree of problems related to drug abuse.ResultsAbility to engage in social roles and activities was positively correlated with overall well-being (r = .49, p <.05) and negatively correlated with degree of problems related to drug abuse (r = −.19, p <.05). Mediation analysis revealed that PERMA fully mediated the relationship between ability to engage in social roles and activities and degree of problems related to drug abuse, with accomplishment emerging as a significant indirect pathway (Effect = −0.05). The model explained 17% of the variance in degree of problems related to drug abuse.ConclusionsFindings underscore the importance of well-being, particularly accomplishment, in the relationship between veterans’ ability to engage in social roles and activities and degree of problems related to drug abuse. Interventions integrating well-being frameworks may offer holistic approaches to recovery for veterans with SUDs and mental illnesses. Future research should explore longitudinal effects of PERMA-focused interventions.